Structural properties of Cyclopentanone-bridged Bis-Macrocyclic Ligand Dicopper(II) complexes in the solid and in solution: a successful test of the MM-EPR method - Comba, Peter; Kerscher, Marion (Inorganic chemistry, 2003)
The copper(II)-assisted condensation of 2,3,2-tet (3,7-diazanonane-1,9-diamine) with formaldehyde and cyclopentanone yields the mono- and bis-macrocyclic Mannich condensation products L1 and L2, as well as the Schiff-base product L3, all with cyclam-type tetraaza macrocycles, coordinated to copper(II). The combination of molecular mechanics and EPR spectroscopy (MM-EPR) reveals that all three isomers of [Cu2(L2)(OH2)n]2+ (n = 0−4), with the expected trans-III (R,R,S,S) configuration of the 14-membered tetraaza macrocycles, are of similar stability, and that the isomer whose structure is solved by X-ray crystallography has a different structure in solution.
Gesehen am 21.02.2018